Nursing Care For Mental Health With Sensory Perception Disorders: Hallucinations In Schizophrenia Patients - Ariyanti, Sri; Abdullah, Abdullah; Wahyuni, Ria; Halmar, Halbina Famung; Hoda, Ferdinandus Suban; Nursinah, A.; Ramadhani, Safrina; Jabir, M. Agus; Sapnita, Sapnita; Saodah, Siti (International Journal of Health Sciences, 2025)
Hallucinations are a symptom of mental disorders. Patients experience changes in sensory perception, experiencing false sensations of sound, sight, taste, touch or smell. Patients feel stimuli that are not actually there. The purpose of this study was to provide psychiatric nursing care to patients with sensory perception disorders Hallucinations. The research method is a case study by studying patient cases directly using the nursing process approach. Continued with data collection techniques. The results state that the nursing problems found, in cases of auditory hallucination patients based on theory there are three nursing diagnoses , namely: Risk of harming oneself, others, and the environment related to auditory hallucinations that Changes in sensory perception: auditory hallucinations related to withdrawal; Impaired social interaction: Withdrawal related to Low self-esteem. The conclusion obtained is that there is an increase in the patient's ability to control the hallucinations experienced and the impact on reducing the symptoms of auditory hallucinations experienced.